2016
DOI: 10.4110/in.2016.16.6.330
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells in Hepatitis B and C Virus Infections

Abstract: Hepatitis B virus (HBV) and hepatitis C virus (HCV) are hepatotropic viruses that establish chronic persistent infection by effectively escaping the host immune response and can cause immune-mediated liver injury. It has recently become apparent that regulatory T (Treg) cells, specifically CD4+CD25+Foxp3+ Treg cells, modulate viral diseases by suppressing antiviral immune responses and regulating inflammatory host injury. The roles of Treg cells in HBV and HCV infections range from suppressing antiviral T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 62 publications
4
65
0
Order By: Relevance
“…Currently, Treg and MDSC represent two immunosuppressive cell populations that have been recognised as crucial players in the establishment of immune tolerance and in attenuation of effector cell responses, particularly in tumour microenvironment . While different studies have indicated Treg as important suppressive mediators of T‐cells during CHI, the relevance of MDSC in this disease setting and whether there exist any functional cross‐talk between MDSC and Treg remains enigmatic. A significant increase in Treg frequency had been detected in chronically HBV‐infected patients and it had been suggested that Treg could be induced through repetitive and prolonged stimulation of T‐cells by high concentrations of HBV‐antigen .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, Treg and MDSC represent two immunosuppressive cell populations that have been recognised as crucial players in the establishment of immune tolerance and in attenuation of effector cell responses, particularly in tumour microenvironment . While different studies have indicated Treg as important suppressive mediators of T‐cells during CHI, the relevance of MDSC in this disease setting and whether there exist any functional cross‐talk between MDSC and Treg remains enigmatic. A significant increase in Treg frequency had been detected in chronically HBV‐infected patients and it had been suggested that Treg could be induced through repetitive and prolonged stimulation of T‐cells by high concentrations of HBV‐antigen .…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral‐induced Tregs are produced under particular conditions of antigen exposure and are subdivided into (a) FOXP3 + Treg (iTreg) and (b) FOXP3 − Treg, which includes type‐1 regulatory T‐cells (Tr1) and T‐helper type‐3 cells (Th3) that mediate suppression via interleukine‐10 (IL‐10) and transforming growth factor beta (TGF‐β)‐dependent mechanisms respectively . A marked elevation in CD4 + CD25 + FOXP3 + Treg frequency had been reported in patients with chronic hepatitis B (CHB) and had been shown to inhibit the proliferation and interferon gamma (IFN‐γ) production of HBV‐specific T‐cells and to delay the recruitment of macrophages and dendritic cells to HBV‐infected liver . Furthermore, a recent study demonstrated that Tr1‐cells suppress germinal center formation and anti‐HBV antibody production in HBV‐carrier mice .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in contrast to studies with NSV, IL-10 deficiency affected outcomes by a combination of increased Th1-mediated rather than Th17mediated immunopathogenesis and delayed production of antiviral antibody in the CNS, which is important for viral clearance. Many cells can produce IL-10, but regulatory T cells play a major role during viral infections of multiple organs, including the CNS (21,(32)(33)(34)(35), and are important determinants of NSV infection outcome in susceptible and resistant strains of mice (20). SINV-induced neurologic disease is a manifestation of the inflammatory response to infection rather than virus replication per se (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory T (Tregs) cells are a subset of CD4+ T cells that express the transcription factor Foxp3; they have potent immunosuppressive properties and are critically involved in transplant survival . However, the suppressive properties of Tregs can also lead to persistence of antigens and are associated with decreased clearance of chronic infections such as hepatitis B and C . Additionally, there is increasing evidence that inhibitory molecules such as PD‐1 may play a role in development of Tregs by altering the plasticity of Th1 cells, impairing cell‐mediated immunity …”
Section: Introductionmentioning
confidence: 99%